Coronavirus disease (COVID-19) and unexpected world health crisis - Islam, Md. Zahidul; Anzum, Rabeya; Norullah, Md.; Jahan, Asma (Asian and African Research centre, 2020)
Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus and it has created unexpected world crisis which never happen after second world war. On 30 January 2020, the Director-General of the World Health Organization (WHO) declared the outbreak of COVID-19 to be a Public Health Emergency of International Concern and issued a set of Temporary Recommendations. There is a new public health crisis threatening the world with the emergence and spread of 2019 novel coronavirus (2019-nCoV) or the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The virus originated in bats and was transmitted to humans through yet unknown intermediary animals in Wuhan, Hubei province, China in December 2019. The objective of the paper is to identify the reason to spread COVID-19 and to identify the possible solution to prevent COVID-19. It is a qualitative research. The information has collected studying articles, books and newspapers. People can recover from the coronavirus disease (COVID-19). Catching the new coronavirus does not mean you will have it for life. Most of the people who catch COVID-19 can recover and eliminate the virus from their bodies.